Um olhar crítico e dialógico entre a educação prisional, o ensino de ciências e o preparo do reeducando para a sua ressocialização e reintegração à sociedade - Rosolen, Jussara Maria da Silva (2022)
Brazil, the country with the third largest prison population in the world, lacks reflection, study and dialogue on Prison Education. In addition, there is still little research on pedagogical practices and theories on this topic that is so relevant to the construction of a more egalitarian society. The first researches were motivated by the need to review the search for models that can raise the awareness of the reeducated for their return to life in society. This research was guided by the methodology of qualitative and descriptive bibliographic research. Listing the concepts arising from government agencies, laws, practices and theories to rethink the inclusion of reeducating and their social journey in order to build a new beginning. It was also sought to rethink the Education of Youth and Adults in the prison context, which awakens and stimulates the criticality of the reeducated. The objective of the research was to demonstrate how education can break this cycle of crime, helping to break and help in resocialization and social reintegration, providing people serving time in the prison system with concrete opportunities to rewrite their proposed life trajectory. Thus, it was reflected on how Prison Education, used in the prison system, transforms and includes this subject/re-educating in society and also how Paulo Freire's Liberating Pedagogy motivates the rescue of the feeling of belonging, of returning to the family, and of the role of re-socialization and reintegration of the re-educated in society. It is also essential to understand the challenges of creating projects and actions for the awareness of the reeducating/subject as a social and global being, in this way, the selected studies were analyzed from the use of the concepts of Liberating Pedagogy - based on Freirean Pedagogy. From this research on Portal Capes and Google Scholar, only ten articles published in the last ten years on Prison Education and Science Teaching were found, which not all bring aspects related to dialogue, social transformation and problematization advocated by Paulo Freire. Thus, it was still recognized a long way for a more effective resocialization and also an opportunity for new studies regarding the contribution of Science Teaching in this sense.